The pursuit of the ideal self: An investigation of the relationship of authenticity and ideal self-congruence - Adnan Zogaj; Philipp M. Mähner; Dieter K. Tscheulin (Journal of Consumer Behaviour, 2024)
Research suggests that authentic branding strategies should focus on consumers' actual self rather than their ideal self; that is, brands that match consumers' ideal self are perceived as too psychologically distant from their present self and, thus, as inauthentic. This study challenges this prevailing notion by proposing the novel perspective that ideal self-congruence is more influential than actual self-congruence in driving authenticity. Contrary to the view that brands matching consumers' ideal self are deemed inauthentic due to psychological distance, our research, encompassing four empirical studies, demonstrates that ideal self-congruence significantly enhances positive authentic pride while effectively reducing negative hubristic pride more than actual self-congruence. Furthermore, this study not only reveals that ideal self-congruence is more strongly associated with authentic pride than actual self-congruence but also reshapes the theoretical understanding of the role of self-congruence in the realm of authenticity. Our findings therefore contradict previously cited but hardly empirical arguments by demonstrating that ideally self-congruent brands positively affect perceived brand authenticity more than actually self-congruent brands. Thus, we recommend brands to focus authentic marketing strategies on consumers' ideal self to positively influence consumer behavior.
Keywords: 320